(untitled) (Contemporary Mathematics, 2024)
Let (π, H) be a unitary representation of a locally compact group G. Recent works on some topological centers induced by π have studied. This paper continues the investigation in this regard. The new topological center induced by the module action related to π, which lies between L1(G) and the second dual L1(G)∗∗, is studied. As well, some unitary representations are presented whose topological centers in our sense are L1(G), L1(G)∗∗, or neither.